Implikasi Hukum Pembentukan Peraturan Pelaksana Pasca Putusan Mahkamah Konstitusi Atas Pengujian Undang-Undang No. 11 Tahun 2020 Tentang Cipta Kerja - Rizki, Muhammad; Alwan, Sultan; Rumkel, Nam (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to examine the legal status and binding force of the Implementing Regulations enacted and analyze the legal implications of the formation of Implementing Regulations post-Constitutional Court Decision No. 91/PUU-XVIII/2020. The research method used is empirical with data collection through literature review, interviews, and supporting theories. The data analysis technique employed is descriptive qualitative. The results of the study indicate that the formation of three Implementing Regulations after Constitutional Court Decision No. 91/PUU-XVIII/2020 in the context of the Omnibus Law on Job Creation lacks legal status and binding force in the enforcement of norms. Moreover, Constitutional Court Decision No. 91/PUU-XVIII/2020, which examined the formal aspects of Law No. 11 of 2020 concerning Job Creation, has wide-ranging implications. Through its decision, the Constitutional Court, particularly in point 7, suspends actions or strategic policies with broad impacts and prohibits the issuance of implementing regulations.